ACCOUNTING PROBLEMS IN CORPORATE DISTRIBUTIONS. - Katz, Wilber G. (The Accounting Review, 1941)
Problems of corporate distributions to shareholders furnish the most fertile field for the study of relations between accounting and law. The paper represents an effort to explore some of these relations rather than to discuss for their own sake the accounting treatment of corporate distributions. No attempt is made to develop the subject comprehensively or systematically. Problems dealt with have been chosen because they afford the best illustrations of the evolution of corporate accounting principles and their influence on corporate financial practice. Much confusion in corporation law and accounting has resulted from an authority frequently granted to corporations issuing no par shares to allocate part of the consideration to paid-in surplus. These statutes have handicapped accountants in their efforts to develop and enforce standards of disclosure as to shareholders' investment and undistributed earnings. Until recently, furthermore, accountants have not generally been astute in marking out their own field of influence in the face of these liberal corporation laws.